Pattern of muscle contraction in different postures among Malaysia pineapple plantation workers - N. F. M., Salleh; Ezrin Hani, Sukadarin; N. K., Khamis; R., Ramli (IOP Publishing, 2019)
Lower extremity disorders is associated with prolonged and awkward postures such as kneeling, squatting and stooping. Current study aims to examine the risk factors of awkward postures among pineapple plantation workers in Malaysia by using Ovako Working Posture Analysis System (OWAS). The postural analysis output from OWAS is then compared and validated by using Surface Electromyography (sEMG). There are 103 pineapple plantation workers participated in this study with an average working experience of 1 to 3 years. Based on OWAS findings, it shows for an overall distribution, planting, manual weeding and harvesting are the tasks fell under Action Category (AC) 3 which indicating distinctly harmful and (AC) 4 which indicating extremely harmful. The readings of muscle activity during selected postures show that erector spinae and multifidus muscle are actively contracted during kneeling, squatting and stooping posture. The results from this study signify that long exposure to these postures can increase the likelihood of having WMSDs such as back pain and lower limb injuries among pineapple plantation workers. This study suggests that ergonomic intervention such as mechanization of tools and equipments should be implemented in order to eliminate or reduce poor postures. In case of incapability for any mechanization, adequate and effective training should be provided for the workers as they can apply the knowledge through their job.